The Pleistocene Coyote from the Río Nacaome, Costa Rica - Lucas, Spencer G. (2025)
In 1997, we identified as coyote (Canis latrans) a dentulous left dentary of a canid from the Upper Pleistocene of the Río Nacaome in northwestern Costa Rica. This identification has been questioned based on misconceptions about features of the dentary that supposedly diagnose C. latrans. We reaffirm the identity of the Río Nacaome canid as C. latrans based on long established features of the lower dentition that are diagnostic of C. latrans. We also refute the idea that certain features of the dentary are diagnostic of coyotes. The Nacaome coyote fossil is the only fossil of a coyote from Central America and establishes their late Pleistocene presence well south of records in southern Mexico.